Development and Environmental Sustainability in Nigeria: An African Perspective - Njar, Brian Ifere; Enagu, David Abim (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
This research titled “Development and Environment Sustainability in Nigeria: An African Perspective” examines the effect of development on the African environment. Recent trends and tenets of development are accredited to technological advancements infrastructures and industrialization. Thus, development is respected within the light of social and economic productivity and mostly applauded within the ambiance of consumable scientific, architectural, agricultural and engineering, etc. Notably, the afore-mentioned directly affects the environment and this has become a conundrum to both living and non-living organisms within the environment. It is undisputable that development is good and encouraged, but not at the expense of those to whom it’s meant for. This work then is an exposition of the effects and defects of development that infringes on the environment and proposed a possible solution to environmental sustainability. The paper advocates for a religio-cultural relation with the environment; a relationship that is rather personified than objectified, using Nigeria as a case study. This paper employs the methods of exposition, explication and critical analysis.